The Role of Social Organization in Community Economic Empowerment - Safira Ramadhanitya; Salisah Salsabilla (MUARO RESEARCH: Multidisciplinary Advanced Research Opportunity Journal, 2025)
Social organizations play a significant role in fostering community economic empowerment by acting as a bridge between local communities, government agencies, and private sectors. These organizations function as catalysts for change through capacity-building programs, skill development initiatives, microfinance access, and community-based entrepreneurship projects. By promoting collective action and local participation, social organizations help strengthen social capital and enhance economic resilience. Their activities not only improve income levels but also foster sustainable development by encouraging self-reliance and reducing dependence on external aid. Furthermore, social organizations are instrumental in addressing socio-economic disparities by targeting marginalized groups, promoting gender equality, and facilitating inclusive economic growth. In the era of globalization and rapid technological advancement, the role of social organizations is becoming increasingly relevant, particularly in adapting local communities to changing economic landscapes. This study aims to analyze the strategic role, challenges, and opportunities of social organizations in driving community-based economic empowerment.